Optimizing immunogenicity and product presentation of a SARS-CoV-2 subunit vaccine composition: effects of delivery route, heterologous regimens with self-amplifying RNA vaccines, and lyophilization - Lykins, William R.; Pollet, Jeroen; White, Jessica A.; Keegan, Brian; Versteeg, Leroy; Strych, Ulrich; Chen, Wen-Hsiang; Mohamath, Raodoh; Ramer-Denisoff, Gabi; Reed, Sierra; Renshaw, Christina; Beaver, Samuel; et al. (Frontiers in Immunology, 2024)
IntroductionDozens of vaccines have been approved or authorized internationally in response to the ongoing SARS-CoV-2 pandemic, covering a range of modalities and routes of delivery. For example, mucosal delivery of vaccines via the intranasal (i.n.) route has been shown to improve protective mucosal responses in comparison to intramuscular (i.m.) delivery. As we gain knowledge of the limitations of existing vaccines, it is of interest to understand if changes in product presentation or combinations of multiple vaccine modalities can further improve immunological outcomes.MethodsWe investigated a commercial-stage SARS-CoV-2 receptor binding domain (RBD) antigen adjuvanted with a clinical-stage TLR-7/8 agonist (3M-052) formulated on aluminum oxyhydroxide (Alum). In a murine immunogenicity model, we compared i.n. and i.m. dosing of the RBD-3M-052-Alum vaccine. We measured the magnitude of antibody responses in serum and lungs, the antibody-secreting cell populations in bone marrow, and antigen-specific cytokine-secreting splenocyte populations. Similarly, we compared different heterologous and homologous prime-boost regimens using the RBD-3M-052-Alum vaccine and a clinical-stage self-amplifying RNA (saRNA) vaccine formulated on a nanostructured lipid carrier (NLC) using the i.m. route alone. Finally, we developed a lyophilized presentation of the RBD-3M-052-Alum vaccine and compared it to the liquid presentation and a heterologous regimen including a previously characterized lyophilized form of the saRNA-NLC vaccine.Results and discussionWe demonstrate that i.n. dosing of the RBD-3M-052-Alum vaccine increased IgA titers in the lung by more than 1.5 logs, but induced serum IgG titers 0.8 logs lower, in comparison to i.m. dosing of the same vaccine. We also show that the homologous prime-boost RBD-3M-052-Alum regimen led to the highest serum IgG and bronchial IgA titers, whereas the homologous saRNA-NLC regimen led to the highest splenocyte interferon-γ response. We found that priming with the saRNA-NLC vaccine and boosting with the RBD-3M-052-Alum vaccine led to the most desirable immune outcome of all regimens tested. Finally, we show that the lyophilized RBD-3M-052-Alum vaccine retained its immunological characteristics. Our results demonstrate that the route of delivery and the use of heterologous regimens each separately impacts the resulting immune profile, and confirm that multi-product vaccine regimens can be developed with stabilized presentations in mind.